THE INFLUENCE OF SOCIAL CAPITAL AND INNOVATION CAPABILITY ON CREATIVE INDUSTRY BUSINESS PERFORMANCE - Halim, Fitria; Kusuma, Rr. Chusnu Syarifa Diah; Sherly, Sherly; Loist, Christine; Sudirman, Acai (International Journal of Business, Law, and Education, 2023)
The rapid development of information technology in creative industry businesses forces business people to optimize social capital and innovation capability well. This is what underlies the development of the creative industry so that it can optimize all its resources, especially in the aspects of social capital and innovation capability. This research aims to analyze the influence of social capital and innovation capability on creative industry business performance. Data analysis confirms that social capital and innovation capability significantly affect business performance. The conclusions of this research inform creative industry business players so that they can develop a culture of innovation throughout the organization, encourage employees to share ideas, provide sufficient support and resources, and adopt a flexible and adaptive management approach to be internationally competitive. Through this research, it is hoped that it can provide a fundamental contribution in supporting information regarding strategic steps in optimizing the resources owned by every creative industry business actor, both in terms of social capital and innovation capability in marketing activities.